Handbook of research on counterfeiting and illicit trade - Chaudhry, Peggy E. (Edward Elgar Publishing, 2017)
This unique Handbook provides multiple perspectives on the growth of illicit trade, primarily exploring counterfeits and internet piracy. It includes expert opinion on a wide range of topics including the evaluation of key global enforcement issues, government and private-sector agency initiatives to stifle illicit trade, and the evolution of piracy on the internet. The authors also assess the efficacy of anti-counterfeiting strategies such as targeted consumer campaigns, working with intermediaries in the supply chain, authentication technology, and online brand protection